Passive Q-switching of ∼2.7 µm Er:Lu2O3 ceramic laser with a semiconductor saturable absorber mirror. (17th January 2018) - Ren, Xiaojing; Shen, Deyuan; Zhang, Jian; Tang, Dingyuan
Abstract: We demonstrate the passively Q-switched operation of an Er:Lu2 O3 ceramic laser at ∼2.7 µm for the first time, to the best of our knowledge. By using a semiconductor saturable absorber mirror (SESAM), stable pulse trains with a repetition rate of 20–33.3 kHz are produced in a compacted v-shaped resonator. The pulse duration (FWHM), pulse energy, and peak power are 660 ns, 1.8 µJ, and ∼2.73 W, respectively, at 33.3 kHz repetition rate. Prospects for further improvements in terms of laser performances are discussed.